Morphology and Dynamics of Federalism - Suchecki, Wiktor (Czasopismo Prawno-Historyczne, 1980)
I. In view of the fact that in principle the primary aim of federation, namely to assure maximum unity of action while preserving historically justified rights of the component parts to autonomy, is always the same, reflection should be given to an ideal type of federation, most closely corresponding to the need of assuring unity on the one hand, and political pluralism on the other. It seems that such a theoretical model could best be built on grounds of a specific political system, which would take in account both social forces favouring integration and those conducive to disintegration. Such an ideal model must be distinguished from an empiric model corresponding more or less accurately to synthetically formulated historical characteristics of federal states. In the early period of emergence of modern federal states, the ideal type of federation of necessity coincided almost exactly with the empirically existing federal state. The federal system of the United States was viewed for a time as the ideal model of a federal state, until it was found that transplantation of the American model to Europe for example, in most cases was impracticable or simply pointless.